2007
DOI: 10.3748/wjg.v13.i8.1257
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of ether à go-go potassium channel in colorectal cancer patients and cell lines

Abstract: AIM:To study the expression of ether à go-go (Eag1) potassium channel in colorectal cancer and the relationship between their expression and clinico-pathological features. METHODS:The expression levels of Eag1 protein were determined in 76 cancer tissues with paired noncancerous matched tissues as well as 9 colorectal adenoma tissues by immunohistochemistry. Eag1 mRNA expression was detected in 13 colorectal cancer tissues with paired non-cancerous matched tissues and 4 colorectal adenoma tissues as well as tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…The restricted extra neural expression of the channel conflicts with the observation that the majority of tumors of almost every stem express the channel [47][48][49][50][51][52][53][54][55][56][57][58]. Our own studies of over 700 samples from human tumors of diverse origin indicated that the channel is expressed in over 70% of the samples, while meta-analysis of published data reflects this high frequency of K V 10.1 expression in ~1500 reported cases.…”
Section: Expression Of K V 101 In Tumor Tissues Diagno-stic Potentialcontrasting
confidence: 69%
“…The restricted extra neural expression of the channel conflicts with the observation that the majority of tumors of almost every stem express the channel [47][48][49][50][51][52][53][54][55][56][57][58]. Our own studies of over 700 samples from human tumors of diverse origin indicated that the channel is expressed in over 70% of the samples, while meta-analysis of published data reflects this high frequency of K V 10.1 expression in ~1500 reported cases.…”
Section: Expression Of K V 101 In Tumor Tissues Diagno-stic Potentialcontrasting
confidence: 69%
“…In our previous study, expression level of Eag1 protein in colorectal cancer was found depending on the tumor size, lymphatic node metastasis, other organs metastasis and Dukes' stage, but not depending on sex, age, site and degree of differentiation [24]. Data reported here reveal that there was significant correlation between Eag1 protein expression and depth of penetration in ESCC, although not associated with other clinicopathological factors.…”
Section: Dsicussionsupporting
confidence: 42%
“…In fact, Eag1 potassium channels were found to be aberrantly expressed in cervical cancer [21], gliomas [22], soft tissue sarcoma [23], colorectal cancer [24], esophageal cancer and other tumors from diverse origin [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although implicated in tumour development rather than cell invasion/metastases, SLC5A8, a sodium symporter identified by a global search for genes that were aberrantly methylated at high frequency in human colon cancer and consequently repressed in expression (Li et al, 2003), was characterised as a candidate tumour suppressor. Finally, and reminiscent of our findings with CLCN4, expression of the ether a go-go (Eag1) potassium channel is linked with tumour metastases, in that its expression correlates with lymphatic node metastases and organ metastases (Ding et al, 2007). However, whether Eag1 is a driver of tumour spread or merely a passive bystander remains to be determined.…”
Section: Discussionmentioning
confidence: 70%
“…These findings, and others (Soroceanu et al, 1999;Bustin et al, 2001;Chapman et al, 2002;Li et al, 2003;Ding et al, 2007), should direct attention to the importance of ion exchangers in tumour progression and could provide new avenues for managing patients at high risk for metastatic spread.…”
Section: Discussionmentioning
confidence: 99%